Flexural Behavior of Precast Concrete Segmental Box-Girders with Dry Joints - Shun Chai; Tong Guo; Zheheng Chen; Jun Yang (Advances in Civil Engineering)
Precast concrete segmental (PCS) box-girders are widely used in bridge construction, while studies on flexural behaviors of PSC box-girders with dry joints are insufficient. Six large-scale PCS box-girders with dry joints were tested to failure under two-point loading in this study. Strain increments, tendon forces, deflections at mid-span, and cracks were recorded during the tests. Multiple factors were investigated with regards to their influence on flexural performance of girders. It is found that most specimens failed due to the excessive force in tendons, while the specimen with external tendons failed due to concrete compressive crushing. Larger shear span ratio resulted in greater increase in tendon force and concrete strain during loading and, accordingly, the lowest ultimate flexural capacity. Lower concrete strength resulted in larger increase in concrete strain and tendon force during loading and relatively smaller deflection at failure. For the specimen with four segments, a significant increase in tendon force and smaller deflections at failure was observed as compared with specimen 1, though the failure load was similar. Numerical simulation is further conducted, where it is found that the area of prestressed tendon and the number of joints have a significant influence on ultimate flexural bearing capacity and deflection; besides, deflection control standard of PCS girders should be stricter than that of the integral cast girder. The corbel joints, in general, show better ultimate performance than the castle-shaped joints.